A study of the determination of goşsypol levels of cottonseed meals produced in turkey - Şakir Doğan TUNCER; Sakine YALÇIN (Eurasian Journal of Veterinary Sciences)
This experiment was carried out to determine free and total gossypol contents of cottonseed meals obtained from the different parts of Turkey. Cottonseed meal plays an important role in supplying the protein needs of animals. However gossypol content, especially free gossypol content, is a restricted factor for the usage of this meal. At the end of the experiment, free and total gossypol amounts of extraction cottonseed meal were found as 0.0573 and 0.418%; the amounts of expeller cottonseed meal were also found as 0.0694 and 0.565%, respectively.